An in-mold composite coating for injection molding, its preparation method and application
Patent Information
- Application Number
- CN202611191151.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-09-18
AI Technical Summary
[0004]然而,由于注塑模具工作时,型腔内部为200~300℃、10~100MPa的高温高压环境,有机物长期处于该环境中会逐渐碳化变质,因此现有的模内涂层一般为陶瓷涂层、金属涂层等耐高温涂层,而鲜有有机涂层
1)本发明的底层为交联增强的PEDOT:PSS导电层,提供稳定的导电通路以及与模具钢的良好附着力,底层中的交联网络可抑制PEDOT:PSS在水蒸气中的溶胀。NH2-CNT提供一维长程导电通道和力学增强,MoSi2提供零维短程导电节点和耐高温支撑,二者形成点线互补的协同导电网络。实验证明,CNT与MoSi2同时添加时的耐高温性能(250℃ ΔR=58.3%)远优于单独添加CNT(345.3%)或单独添加MoSi2(187.4%),具有协同效应。表层为全氟聚醚硅烷疏水保护层,隔绝水汽侵蚀,同时保持低表面能。底层与表层之间存在化学键合(PFPE-silane的硅烷端与底层残余羟基缩合),形成双层协同:表层保护底层免受水汽直接侵蚀,底层为表层提供稳定的支撑基底,二者共同实现了长效抗静电与防凝露功效。本发明的复合涂层在表面电阻率(3.5×102Ω/sq)、耐湿热(168h ΔR=65.1%)、耐高温(250℃ ΔR=58.3%)、附着力(5B)和防凝露(水接触角112.5°)等方面均达到优异水平,可以抑制湿热车间连续注塑时出现的静电吸灰或冷凝水缺陷情况,能够提高注塑产品的良品率,具有长效抗静电与防凝露的功效。
Smart Images

Figure CN122772415A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of in-mold coating technology for injection molds, specifically to a moisture- and heat-resistant, antistatic composite coating for injection molds, its preparation method, and its application. Background Technology
[0002] Injection mold production is significantly affected by ambient temperature and humidity. In some regions, summer workshop temperatures can reach above 35°C and relative humidity above 85%RH. The injection molding process further increases the workshop temperature, leading to a significant decrease in yield rates during continuous injection molding operations. The main reason is that when hot, humid air comes into contact with low-temperature areas of the mold (such as near condensate pipes), condensation occurs rapidly. When water droplets enter the mold cavity, injection molding can cause defects such as flow marks, silver streaks, and bubbles on the product surface. In severe cases, it can cause short circuits or poor insulation. This often occurs during startup or near the cooling water inlet. Furthermore, in high humidity environments, a layer of water film adheres to the mold surface, hindering charge leakage and exacerbating static electricity buildup. This leads to increased static dust attraction, with dust accumulation actually increasing.
[0003] In-mold coating (IMC) is an emerging injection molding process widely used in the injection molding production of precision connectors such as automotive connectors and industrial waterproof connectors. It involves pre-coating a functional layer inside the cavity of an injection mold to improve the quality of the molded parts or increase the production efficiency of the mold itself. For example, Suzhou Jiheng Nanotechnology Co., Ltd. has disclosed a physical vapor deposition (PVD) coating, which deposits an extremely thin, hard, and wear-resistant ceramic coating on the surface of a plastic mold to improve the surface properties of the mold, extend its service life, and improve the production quality and efficiency of plastic products. Mode Group has disclosed a non-electroplated nickel-Teflon nano-coating that can uniformly cover complex cavity surfaces, saving injection molding cycles and improving production efficiency.
[0004] However, during injection mold operation, the cavity is exposed to a high-temperature and high-pressure environment of 200-300℃ and 10-100MPa. Organic materials exposed to this environment for extended periods will gradually carbonize and deteriorate. Therefore, existing in-mold coatings are generally high-temperature resistant coatings such as ceramic coatings and metal coatings, with few organic coatings. This results in current injection mold in-mold coatings generally having limited functions. For example, while ceramic coatings such as Al2O3 and ZrO2 possess excellent high-temperature and corrosion resistance, they lack conductivity and cannot eliminate static electricity. Conductive coatings such as conductive carbon black and graphene paint can solve the problem of static dust attraction, but they are thick, not resistant to humidity and heat, carbon materials are prone to oxidation, the coating absorbs water and blisters, and has poor hydrophobicity, failing to prevent condensation. Furthermore, these existing coatings are mostly prone to absorbing water and swelling under humid and hot conditions, leading to the breakage of the conductive network, a sharp increase in resistivity, and a decrease in adhesion, resulting in blistering and peeling of the coating.
[0005] Therefore, there is currently no in-mold coating that is resistant to high temperature and high pressure and suitable for continuous injection molding in humid and hot environments, providing protection against condensation and static electricity. Summary of the Invention
[0006] One of the objectives of this invention is to provide an in-mold composite coating for injection molds, which at least achieves the effects of strong coating adhesion, high temperature and high pressure resistance, long-lasting antistatic effect and anti-condensation.
[0007] The objective of this invention is achieved through the following technical solution: An in-mold composite coating for injection molds includes a bottom conductive layer and a top hydrophobic layer. The conductive layer comprises nano-conductive filler, nano-molybdenum disilicide (MoSi2), conductive polymer, and crosslinking agent; The nano-conductive filler includes at least one of carbon nanotubes, metal nanowires, and conductive whiskers; the nano-conductive filler is aminated before being added; the conductive polymer includes at least one of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate (PEDOT:PSS), polyaniline, and polypyrrole; the crosslinking agent includes at least one of (3-glycidoxypropyl)trimethoxysilane (GOPS), (3-glycidoxypropyl)triethoxysilane, and γ-glycidoxypropylmethyldiethoxysilane.
[0008] The hydrophobic layer comprises a fluorosilane compound; the fluorosilane compound comprises perfluoropolyether silane (PFPE-silane) or tridecafluorooctyltriethoxysilane (FAS-13).
[0009] In some embodiments, the thickness of the conductive layer is 100-300 nm; the thickness of the hydrophobic layer is 20-50 nm. The coating thickness is controlled by the coating process parameters.
[0010] It is worth noting that the internal temperature of injection mold cavities can reach 200-300℃ during operation, and extremely high pressure is generated. Therefore, the cavity coating needs to have strong heat resistance and pressure resistance. However, most conductive polymers have poor long-term heat resistance. For example, the conductivity of PEDOT:PSS decreases rapidly and eventually loses its conductivity when exposed to environments above 200℃. Therefore, although there are reports of composite antistatic coatings of carbon nanotubes, PEDOT:PSS, and GOPS (such as Taiwan patent TWI777158B), this technology is mainly aimed at room temperature or low temperature applications such as biomedicine and flexible electronics. Its coating lacks high-temperature resistant components and anti-condensation functional layers, and cannot meet the extreme operating conditions of injection mold cavities at 200-300℃ and 10-100MPa.
[0011] Based on this, the present invention also incorporates molybdenum disilicide nanoparticles. Carbon nanotubes in the material possess high mechanical strength and axial thermal conductivity, enabling rapid heat dissipation of the conductive layer and improving mechanical strength; however, they are costly and have poor dispersibility. Molybdenum disilicide possesses dual characteristics of metals and ceramics, exhibiting a high melting point (2030℃), good electrical conductivity, and excellent high-temperature oxidation resistance; however, its mechanical strength is unstable and significantly affected by temperature. This invention synergistically modifies carbon nanotubes and molybdenum disilicide by mixing them, forming complementary one-dimensional linear and zero-dimensional dot-like conductive networks within the PEDOT:PSS matrix. Carbon nanotubes provide long-range conductive channels and mechanical reinforcement, while molybdenum disilicide fills the voids in the CNT network, providing short-range conductive nodes and high-temperature support. Furthermore, MoSi2 already possesses a surface oxide layer at room temperature, which contains active Si-OH groups. These naturally occurring Si-OH groups undergo a condensation reaction with the silane ends of GOPS during the coating curing process, allowing molybdenum disilicide to embed into the Si-O-Si crosslinking network of the conductive polymer through chemical bonds, further improving the tightness of the connection with the crosslinking agent and extending the service life of the coating.
[0012] This invention utilizes the synergistic effect of carbon nanotubes and molybdenum disilicide to enable the nanoscale conductive layer to withstand the high-temperature and high-pressure environment within the mold cavity during compression molding. As for the hydrophobic layer, perfluoropolyether silane itself possesses good heat resistance, requiring no additional modification.
[0013] This invention uses a silane coupling agent as a crosslinking agent, and its crosslinking mechanism is as follows: 1. The epoxy group of the crosslinking agent undergoes a ring-opening reaction with the active groups in the conductive polymer (such as the sulfonic acid groups in PEDOT:PSS, the amino groups in polyaniline, and the imino groups in polypyrrole), realizing chemical crosslinking between the conductive polymer molecular chains and inhibiting their swelling in water vapor; 2. The epoxy group of the crosslinking agent undergoes a nucleophilic ring-opening reaction with the amino groups on the surface of the aminated filler (such as aminated carbon nanotubes), forming CN bonds, which covalently bond the filler to the crosslinking network; 3. The silane end of the crosslinking agent and the inner wall of the cavity containing active hydroxyl groups form Si-OM bonds through condensation, realizing a firm anchoring between the coating and the mold steel. Through the above multiple crosslinking pathways, the crosslinking agent connects the poorly compatible nano-conductive filler, molybdenum disilicide, and conductive polymer to form a dense crosslinking network.
[0014] A second objective of this invention is to provide a method for preparing the in-mold composite coating of the injection mold, as follows: S1: Activation pretreatment of the cavity interior of the injection mold; S2: Add crosslinking agent, conductive enhancer, nano-molybdenum disilicide and aminated carbon nanotubes to the dispersion of the conductive polymer, filter, and then coat the filtrate onto the inner surface of the cavity, and cure by gradient heating to form the conductive layer. S3: The fluorosilane compound is heated and evaporated for vapor deposition to form a self-assembled monolayer on the surface of the conductive layer, and then annealed to form the hydrophobic layer.
[0015] In some embodiments, in step S1, the activation pretreatment specifically involves: polishing the inner surface of the cavity, ultrasonically cleaning it with an organic solvent, and then performing oxygen plasma treatment to introduce hydroxyl groups onto the inner surface of the cavity.
[0016] In some examples, the coating method is spin coating, with a spin coating speed of 1000-3000 rpm and a spin coating time of 30-90 s.
[0017] In the example, the coating method is spraying, using air spraying, with a spraying pressure of 0.2 to 0.5 MPa, a spraying distance of 150 to 250 mm, and 2 to 5 spraying times.
[0018] In some embodiments, in step S2, the conductive enhancer includes at least one of dimethyl sulfoxide (DMSO), ethylene glycol (EG), ethanol (EtOH), and isopropanol (IPA); The filtration process uses a 0.45μm filter membrane; The gradient temperature curing process includes sequentially holding at 80~90℃ for 15~25 min, at 120~150℃ for 20~40 min, and at 155~165℃ for 5~15 min.
[0019] In some examples, the amounts of the crosslinking agent, the conductive reinforcing agent, the aminated carbon nanotubes, and the nano-molybdenum disilicide are 1-5 wt%, 1-6 vol%, 0.5-2 wt%, and 0.5-1.2 wt%, respectively, with the balance being the conductive polymer.
[0020] In some embodiments, in step S3, the temperature of the heating and evaporation is 110~130°C; The vapor deposition time was 30 minutes. The annealing temperature is 150~180℃, and the annealing time is 15~40min.
[0021] The third objective of this invention is to provide an application of the aforementioned in-mold composite coating for injection molds: to improve the moisture and heat resistance and antistatic properties of injection molds, and to increase the yield of injection molded products produced under high temperature and high humidity conditions.
[0022] In some embodiments, the injection mold includes a two-plate or three-plate type, and a grounding copper foil is provided on the parting surface, wherein the grounding copper foil overlaps with the composite coating inside the injection mold.
[0023] In some embodiments, a drainage groove is provided at the bottom of the cavity of the injection mold.
[0024] It is worth noting that the overlap between the grounding copper and the composite coating underlayer ensures the rapid dissipation of static charge conducted from the conductive layer, while the drainage channel collects and guides trace amounts of condensate for timely discharge. When the coating is partially damaged, it can be repaired through localized cleaning, plasma treatment, and recoating of the underlayer and surface layers, without requiring the entire mold to be scrapped.
[0025] The beneficial effects of this invention are as follows: 1) The bottom layer of this invention is a cross-linked reinforced PEDOT:PSS conductive layer, providing a stable conductive path and good adhesion to the mold steel. The cross-linked network in the bottom layer can inhibit the swelling of PEDOT:PSS in water vapor. NH2-CNT provides one-dimensional long-range conductive channels and mechanical reinforcement, while MoSi2 provides zero-dimensional short-range conductive nodes and high-temperature support. The two form a complementary point-line synergistic conductive network. Experiments have shown that the high-temperature resistance performance (250℃ ΔR=58.3%) when CNT and MoSi2 are added simultaneously is far superior to adding CNT alone (345.3%) or adding MoSi2 alone (187.4%), demonstrating a synergistic effect. The surface layer is a perfluoropolyether silane hydrophobic protective layer, isolating water vapor erosion while maintaining low surface energy. There is a chemical bond between the bottom layer and the surface layer (the silane end of PFPE-silane condenses with the residual hydroxyl groups of the bottom layer), forming a double-layer synergy: the surface layer protects the bottom layer from direct water vapor erosion, and the bottom layer provides a stable supporting substrate for the surface layer. Together, they achieve long-lasting antistatic and anti-condensation effects. The composite coating of this invention has a surface resistivity of 3.5 × 10⁻⁶. 2 It achieves excellent levels in terms of resistance to Ω / sq, damp heat (168h ΔR=65.1%), high temperature (250℃ ΔR=58.3%), adhesion (5B), and anti-condensation (water contact angle 112.5°). It can suppress electrostatic dust attraction or condensation defects that occur during continuous injection molding in humid and hot workshops, improve the yield of injection molded products, and has long-lasting antistatic and anti-condensation effects.
[0026] 2) All processes of this invention are carried out below 180°C, requiring no vacuum equipment, with no VOC emissions, meeting environmental protection requirements, and the coating thickness is extremely thin, without changing the cavity precision; it can be used for the modification of existing molds or the manufacture of new molds. Attached Figure Description
[0027] Figure 1 This is a schematic diagram of the composite coating structure inside the injection mold of the present invention. Detailed Implementation
[0028] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings, but the scope of protection of the present invention is not limited to the following description.
[0029] Example 1 This embodiment is used to prepare an in-mold composite coating for injection molds, and the specific method is as follows: 1) Take a P20 mold steel sample, polish the surface to Ra≤0.1 μm, and ultrasonically clean it with acetone and ethanol for 15 min each, then dry it with nitrogen. Then put it into a plasma cleaner for oxygen plasma treatment to introduce active hydroxyl groups into the inner surface of the cavity. The power is 100W, the oxygen flow rate is 50 sccm, and the time is 3 min.
[0030] 2) Take 10 mL of commercially available PEDOT:PSS aqueous dispersion (Clevios PH1000), and add 5 vol% DMSO, 3 wt% GOPS, 0.7 wt% NH2-CNT and 0.8 wt% MoSi2 (particle size 30 nm) in sequence. Stir magnetically for 2 h until uniformly dispersed to prepare a conductive solution. Then filter it through a 0.45 μm PTFE filter membrane. Coat the filtrate onto the inner surface of the pretreated mold at 2000 rpm for 1 min. Then perform step curing (pre-curing at 85℃ for 20 min, main curing at 135℃ for 30 min, and post-curing at 160℃ for 10 min) to form a cross-linked conductive underlayer.
[0031] 3) Place the mold coated with the substrate into a 500mL sealed glass container and add 15μL of perfluoropolyether silane (Fluorolink S10). Heat and evaporate in a 120℃ oven for 30min to allow the silane vapor to self-assemble on the substrate surface. After removal, anneal at 150℃ for 15min to allow the silane ends to condense with the residual hydroxyl groups in the substrate. Rinse with isopropanol for 30s and dry with nitrogen.
[0032] 4) Install the coated cavity back into the injection mold.
[0033] The preparation method of aminated carbon nanotubes is as follows: after acid washing, carbon nanotubes are immersed in pre-hydrolyzed KH-550, reacted at 80℃ for 2 hours, and then centrifuged and washed to obtain the product.
[0034] Examples 2-3 This method is used to provide an in-mold composite coating for injection molds, and the specific method is the same as in Example 1, except that the amount of GOPS used is different, as shown in Table 1: Table 1
[0035] Examples 4-6 This method is used to provide an in-mold composite coating for injection molds, and is the same as in Example 1, except that the amounts of NH2-CNT and nano-MoSi2 are different, as shown in Table 2. Table 2
[0036] Example 7 This method is used to provide an in-mold composite coating for injection molds. The specific method is the same as in Example 1, except that the vapor deposition and annealing treatment in step S3 are not performed, and only the conductive layer is retained.
[0037] Examples 8-10 This method is used to provide an in-mold composite coating for injection molds, and is the same as in Example 1, except that the ratio of NH2-CNT and nano-MoSi2 is different, as shown in Table 3. Table 3
[0038] Example 11 This embodiment provides an in-mold composite coating for injection molds. The specific method is the same as in Embodiment 1, except that the coating method in step 2) is air spraying. The spraying process parameters are: spraying pressure 0.3MPa, spraying distance 200mm, spraying times 3, and flash drying time 30s after each spray. The remaining steps and parameters are the same as in Embodiment 1.
[0039] Comparative Example 1 This comparative example is used to prepare an in-mold composite coating for injection molds. The specific method is the same as in Example 1, except that GOPS (0 wt%) is not added in step 2).
[0040] Comparative Example 2 This comparative example is used to prepare an in-mold composite coating for injection molds. The specific method is the same as in Example 1, except that in step 2), only PEDOT:PSS+DMSO (5 vol%) is used, without GOPS, NH2-CNT, MoSi2, or hydrophobic layer. After spin coating, it is heat-cured at 150°C for 30 min.
[0041] Experimental Example 1 Coating samples from Examples 1-10 and Comparative Examples 1-2 were taken and tested for surface resistivity, adhesion, resistance to damp heat, high temperature resistance, and water contact angle. The specific methods are as follows: 1) Surface resistivity: Four-probe method (ASTM F390-11), five different locations are measured for each sample and the average value is taken.
[0042] 2) Adhesion: Cross-cut test (ASTM D3359), test method B, rating 0~5B.
[0043] 3) Moisture and heat resistance: The test piece was placed in a constant temperature and humidity chamber (ESPEC AR-360) at 85℃ / 85%RH for 168 hours. The surface resistance and water contact angle were measured, and the resistance change ΔR (%) was calculated.
[0044] 4) High temperature resistance: The coated sample was heated at 250°C for 2 hours in air atmosphere and the surface resistivity change rate was tested after natural cooling.
[0045] 5) Water contact angle: Use a contact angle measuring instrument to measure the average value at 5 different locations for each sample.
[0046] The test results are shown in Tables 4 to 7: Table 4. Effect of different GOPS contents on the performance of the conductive layer
[0047] Results Analysis: Without GOPS (Comparative Example 1), although the initial resistivity was low, it increased sharply by 853.5% after 168 hours of humid heat, and the coating showed significant peeling. This was because PEDOT:PSS swelled severely in moisture, leading to the breakage of the conductive network. Adding 1 wt% GOPS improved the humid heat stability somewhat, but it was still not ideal. At a GOPS content of 3 wt%, the adhesion was optimal (5B), and the resistivity change was controlled at 65.1%, exhibiting both good conductivity and humid heat stability. Increasing the GOPS content to 5 wt% further improved the humid heat stability (ΔR = 42.8%), but the initial resistivity increased to 1.2 × 10⁻⁶. 3 The Ω / sq content is likely due to the formation of insulating poly / oligomeric siloxanes in PEDOT:PSS by excess GOPS, which increases charge transport resistance. Considering both conductivity and hygrothermal stability, the preferred GOPS content is 3-5 wt%, more preferably 3 wt%.
[0048] Table 5. Effect of the synergistic effect of NH2-CNT and MoSi2 on electrical conductivity.
[0049] Results analysis: (1) NH2-CNT added alone (Example 5): The addition of NH2-CNT significantly reduced the initial resistivity (from 3.2 × 10⁻⁶). 2 Reduced to 1.8×10 2 The conductivity (Ω / sq) is high because NH2-CNTs form a highly efficient conductive percolation network in the PEDOT:PSS matrix. However, the improvement in high-temperature resistance is limited when NH2-CNTs are present alone (ΔR = 345.3% after heating to 250℃). This is because although NH2-CNTs have excellent intrinsic conductivity, their interfacial bonding with PEDOT:PSS is weak, and the expansion of the polymer matrix at high temperatures can lead to the separation of CNT-CNT contacts.
[0050] (2) MoSi2 added alone (Example 4): The addition of MoSi2 increased the initial resistivity, which may be because the dispersion of MoSi2 nanoparticles in PEDOT:PSS is not as good as that of NH2-CNT, and some particles agglomerate to form insulating regions. However, the high-temperature resistance of MoSi2 added alone is significantly better than that of CNT added alone (ΔR=187.4% after heating at 250℃), which is attributed to the ceramic properties of MoSi2 itself and the chemical stability provided by its natural oxide layer.
[0051] (3) Synergistic addition of NH2-CNT and MoSi2 (Examples 1, 8, 9, 10): When NH2-CNT and MoSi2 are added simultaneously, all performance characteristics are superior to those of adding either filler alone. Particularly noteworthy is that in Example 1, when NH2-CNT and MoSi2 are added simultaneously, the ΔR after heating at 250°C is 58.3%, while the ΔR for adding CNT alone (Example 5) is 345.3%, and the ΔR for adding MoSi2 alone (Example 4) is 187.4%. This indicates that the interaction between NH2-CNT and MoSi2 is not a simple physical mixture, but rather a significant synergistic effect. In particular, the adhesion reaches 5B, far superior to the 3B achieved by adding NH2-CNT alone and the 4B achieved by adding MoSi2 alone. Among all tested combinations, Example 1 (NH2-CNT:MoSi2≈0.7:0.8) exhibits the best overall performance.
[0052] Table 6. Influence of the hydrophobic layer on the overall performance of the composite coating
[0053] Results Analysis: Without the hydrophobic layer (Example 7), the PEDOT:PSS conductive layer is directly exposed to a high humidity environment, allowing water molecules to freely penetrate into the coating, leading to swelling of PEDOT:PSS and damage to the conductive network. The PFPE-silane hydrophobic layer, however, increases the water contact angle from 58° to 112°, effectively blocking the physical penetration of water vapor.
[0054] Table 7 Overall Performance Comparison
[0055] Table 7 shows that the pure PEDOT:PSS coating (Comparative Example 2) exhibits a sharp decline in performance under humid and high-temperature environments, failing to meet the requirements of injection mold cavities. While the gradual introduction of GOPS crosslinking (Example 6), CNT conductivity enhancement (Example 5), and MoSi2 heat resistance enhancement (Example 4) improved various properties to varying degrees, the overall effect was poor. When a complete composite coating (Examples 1, 8, 9, and 10) simultaneously possesses multiple GOPS crosslinking, NH2-CNT / MoSi2 synergistic reinforcement, and a surface PFPE-silane hydrophobic protection, all properties are significantly improved. Example 1 achieves the best overall performance: low surface resistivity (3.5 × 10⁻⁶). 2 With its high Ω / sq, excellent resistance to damp heat (168h ΔR=65.1%), excellent high temperature resistance (250℃ ΔR=58.3%), highest adhesion (5B), and superhydrophobic surface (contact angle 112.5°), it can effectively suppress electrostatic dust and condensation defects that occur during continuous injection molding in humid and hot workshops.
[0056] Furthermore, the initial surface resistivity of the composite coating prepared in Example 11 was 4.1 × 10⁻⁶. 2 The Ω / sq, double 85, 168hΔR is 68.3%, adhesion rating is 5B, water contact angle is 111.2°, which is comparable to the performance of Example 1, indicating that the spraying method is also applicable to the technical solution of the present invention.
[0057] The above description is merely a preferred embodiment of the present invention. It should be understood that the present invention is not limited to the forms disclosed herein and should not be construed as excluding other embodiments. It can be used in various other combinations, modifications, and environments, and can be altered within the scope of the concept described herein through the above teachings or related technologies or knowledge. Modifications and variations made by those skilled in the art that do not depart from the spirit and scope of the present invention should be within the protection scope of the appended claims.
Claims
1. An in-mold composite coating for injection molds, characterized in that: This includes a bottom conductive layer and a top hydrophobic layer; The conductive layer includes nano-conductive filler, nano-molybdenum disilicide, conductive polymer, and crosslinking agent; The hydrophobic layer comprises fluorosilane compounds.
2. The in-mold composite coating for injection molds according to claim 1, characterized in that: The thickness of the conductive layer is 100~300nm; the thickness of the hydrophobic layer is 20~50nm.
3. The in-mold composite coating for injection molds according to claim 1, characterized in that: The nano-conductive filler includes at least one of carbon nanotubes, metal nanowires, and conductive whiskers; the nano-conductive filler is aminated before being added; the conductive polymer includes at least one of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate, polyaniline, and polypyrrole; the fluorosilane compound includes at least one of perfluoropolyether silane and tridecafluorooctyltriethoxysilane; the crosslinking agent includes at least one of (3-glycidoxypropyl)trimethoxysilane, (3-glycidoxypropyl)triethoxysilane, and γ-glycidoxypropylmethyldiethoxysilane.
4. The method for preparing the in-mold composite coating of an injection mold as described in any one of claims 1 to 3, characterized in that: S1: Activation pretreatment of the cavity interior of the injection mold; S2: The crosslinking agent, nano molybdenum disilicide, conductive reinforcing agent and nano conductive filler are added to the dispersion of the conductive polymer, filtered, and then the filtrate is coated on the inner surface of the cavity. The coating is cured by gradient heating to form the conductive layer. S3: The fluorosilane compound is heated and evaporated for vapor deposition to form a self-assembled molecular layer on the surface of the conductive layer, and then annealed to form the hydrophobic layer.
5. The preparation method according to claim 4, characterized in that: In step S1, the activation pretreatment specifically involves: polishing the inner surface of the cavity, ultrasonically cleaning it with an organic solvent, followed by oxygen plasma treatment to introduce hydroxyl groups onto the inner surface of the cavity.
6. The preparation method according to claim 4, characterized in that: In step S2, the conductivity enhancer includes at least one of dimethyl sulfoxide, ethylene glycol, ethanol, and isopropanol; The filtration process uses a 0.45μm filter membrane; The coating process includes spraying or spin coating; the spin coating speed is 1000-3000 rpm, and the spin coating time is 30-90 s; the spraying pressure is 0.2-0.5 MPa, the spraying distance is 150-250 mm, and the number of spraying times is 2-5. The gradient temperature curing process includes sequentially holding at 80~90℃ for 15~25 min, at 120~150℃ for 20~40 min, and at 155~165℃ for 5~15 min.
7. The preparation method according to claim 6, characterized in that: In the dispersion, the crosslinking agent, the conductive reinforcing agent, the nano-conductive filler and the nano-molybdenum disilicide are expressed in proportions of 1-5 wt%, 1-6 vol%, 0.5-2 wt% and 0.5-1.2 wt%, respectively, with the balance being the conductive polymer.
8. The preparation method according to claim 4, characterized in that: In step S3, the heating and evaporation temperature is 110~130℃; The vapor deposition time was 30 minutes. The annealing temperature is 150~180℃, and the annealing time is 15~40min.
9. The application of the in-mold composite coating for injection molds as described in any one of claims 1 to 4, and the in-mold composite coating for injection molds prepared by the preparation method described in any one of claims 5 to 8, in improving the resistance to damp heat and antistatic properties of injection molds, characterized in that: The injection mold includes a two-plate or three-plate type, and a grounding copper foil is provided on the parting surface. The grounding copper foil overlaps with the composite coating inside the injection mold.
10. The application according to claim 9, characterized in that: The bottom of the cavity of the injection mold is provided with a drainage groove.